The assessment of hydrological availability and the payment for ecosystem services: A pilot study in a brazilian headwater catchment - Simedo, Mariana Bárbara Lopes [UNESP]; Pissarra, Teresa Cristina Tarlé [UNESP]; Martins, Antonio Lucio Mello; Lopes, Maria Conceição [UNESP]; Costa, Renata Cristina Araújo [UNESP]; Zanata, Marcelo [UNESP]; Pacheco, Fernando António Leal [UNESP]; Fernandes, Luís Filipe Sanches [UNESP] (MDPI, 2020)
The assessment of water availability in river basins is at the top of the water security agenda. Historically, the assessment of stream flow discharge in Brazilian watersheds was relevant for dam dimensioning, flood control projects and irrigation systems. Nowadays, it plays an important role in the creation of sustainable management plans at the catchment scale aimed to help in establishing legal policies on water resources management and water security laws, namely, those related to the payment for environmental services related to clean water production. Headwater catchments are preferential targets of these policies and laws for their water quality. The general objective of this study was to evaluate water availability in first-order sub-basins of a Brazilian headwater catchment. The specific objectives were: (1) to assess the stream flow discharge of first-order headwater sub-basins and rank them accordingly; (2) to analyze the feasibility of payment for environmental services related to water production in these sub-basins. The discharge flow measurements were conducted during five years (2012 to 2016), in headwaters in a watershed on the São Domingos River at the Turvo/Grande Watershed, represented as the 4th-largest hydrographic unit for water resources management—UGRHI-15 in São Paulo State, Brazil. A doppler velocity technology was used to remotely measure open-channel flow and to collect the data. The discharge values were obtained on periodic measurements, at the beginning of each month. The results were subject to descriptive statistics that analyzed the temporal and spatial data related to sub-basins morphometric characteristics. The discharge flows showed space–time variations in magnitude between studied headwater sub-basins on water availability, assessed based on average net discharges. The set of ecological processes supported by forests are fundamental in controlling and recharging aquifers and preserving the volume of water in headwater in each sub-basin. The upstream inflows influence downstream sub-basins. To avoid scarcity, the headwater rivers located in the upstream sub-basins must not consider basin area as a single and homogeneous unit, because that may be the source of water conflicts. Understanding this relationship in response to conservationist practices installed uphill influenced by anthropic actions is crucial for water security assessment. The headwaters should be considered a great potential for ecosystem services, with respect to the “provider-receiver” principle, in the context of payments for environmental services (PES).
Keywords: Flow; Land use; Payments for environmental services; Riparian forest; Water discharge ecosystem services